Blends of acrylonitrile butadiene rubber/superior processing/natural rubber and poly(vinyl chloride).Part.1.A study of some of the technological properties of NBR/SP rubber/NR/PVC blends - de Silva K G K; Karunanayake L; Muttukkrishnan Krishanthi (Journal of the Rubber Research Institute of Sri Lanka, 1999)
The advantages of using Superior Processing (SP) rubber in place of Natural Rubber (NR) in blends with NBR and NBR/PVC is discussed here in detail. Various technological properties such as tensile, resilence, hardness, compression set, specific gravity, cross-link density and resistance to oil were measured and compared. It is advantageous to use SP rubber in place of NR in the above blends probably due to higher cross-link density in the SP rubber component when compared to NR. It may be possible to use the ternary blends of SP/PVC?NBR in manufacture of injection modable and recyclable products due to their thermoplastic nature.
Keywords: Acrylonitrile butadiene rubber; NBR; NR; PVC blends; SP rubber; Technological property